2016
DOI: 10.18632/oncotarget.9931
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of resistance mutations detectable by next-generation sequencing in TKI-treated lung adenocarcinoma

Abstract: EGFR-mutated lung adenocarcinomas routinely develop resistance to tyrosine kinase inhibitors (TKI). To better characterize the relative frequencies of the resistance mechanisms, we analyzed 48 EGFR-mutated TKI-resistant specimens from 41 patients. Next-generation sequencing of post-treatment specimens detected EGFR p.T790M in 31 (79%) of 39 patients, PIK3CA mutations in 10 (26%), EGFR p.S768_V769delinsIL in one, and KRAS p.G12C in one. Five PIK3CA mutations were outside of codons 542, 545, and 1047. Three of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 51 publications
(75 reference statements)
2
33
0
Order By: Relevance
“…Third, incomplete data on the technical aspects of each procedure precluded analysis of the potential relationship between incidence of molecular analysis failure and the way in which procedures were performed, which would help define optimal conditions to obtain adequate tissue samples. Finally, instead of single-gene tests performed in parallel or sequentially, many centers have now moved to implementing next-generation sequencing-based molecular genotyping [35][36][37][38] ; therefore, the individual molecular success rate at individual genes may not reflect changes in gene testing methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, incomplete data on the technical aspects of each procedure precluded analysis of the potential relationship between incidence of molecular analysis failure and the way in which procedures were performed, which would help define optimal conditions to obtain adequate tissue samples. Finally, instead of single-gene tests performed in parallel or sequentially, many centers have now moved to implementing next-generation sequencing-based molecular genotyping [35][36][37][38] ; therefore, the individual molecular success rate at individual genes may not reflect changes in gene testing methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of epidermal growth factor receptor ( EGFR )-mutated lung carcinomas revealed the existence of multiple resistance mutations in some patients, suggesting the presence of multiple but separate resistant clones or a single cell harbouring multiple resistance mechanisms 50 .…”
Section: What Are the Future Challenges For This Field Of Research?mentioning
confidence: 99%
“…Next-generation sequencing was conducted by using AmpliSeq Cancer Hotspot Panel (v2) (Life Technologies) for targeted multigene amplification as described previously. 20,21 Sequencing data of the targeted genes were analyzed with Torrent Suite (Life Technologies). Mutations were identified and annotated through both Torrent Variant Caller and direct visual inspection of the binary sequence alignment/map (BAM) file on the Broad Institute's Integrative Genomics Viewer (IGV).…”
Section: Next-generation Sequencingmentioning
confidence: 99%